Satire in Sonallah Ibrahim's The Committee: an allegory to ridicule capitalism - Alkodimi, Khaled A.; Omar, Noritah (Penerbit Universiti Kebangsaan Malaysia, 2010)
Despite the voluminous amount of research on the genre of satire, little is known about Arabic satirical texts. This paper explores the satirical devices employed in Sonallah Ibrahim’s novel, The Committee (2001). Through the means of satire, Ibrahim skilfully explores the devastating effects of global capitalism on third world nations, by unravelling the mask that shields the domination and exploitation of Egypt. The discussion seeks to identify the hegemonic and the exploitative nature of the capitalist system on third world countries, specifically the creation of a web of conspiracy that controls the economic and governmental policies of Egypt through multi-national corporations as seen in The Committee. The discussion will show that said corporations ultimately transformed Egypt into a mere consumer market. The discussion concludes with the significance of satire as a mode of expression that is employed to bring about awareness among the public of the destructive consequences of capitalism on Arabic society.